Response of okra (Abelmuschus esculenthus L. Moench) to combined organic and inorganic foliar fertilizers - A. I. Afe; F. Oluleye (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Aim This study investigated the effects of combined organic poultry manure (PM) and inorganic foliar fertilizer (FF) on growth and yield of okra (Abelmuschus esculenthus L. Moench). Materials and methods Field trials were carried out at Shao and Teaching and Research Farm of Kwara State University, Malete, respectively, in 2013 and 2014 cropping seasons. The treatment consisted of PM at 10.0 t/ha, combinations of FF with 10.0, 7.5, 5.0, or 2.5 t/ha, FF alone and control without fertilizer arranged in a randomized complete block design and replicated three times. Results Combinations of PM and FF influenced the growth and fruit yield of okra. PM at 10.0 t/ha plus FF produced the highest plant height of 48.40 and 58.50 cm in 2013 and 2014, respectively. Also, highest number of fruits per plant and fruit yield was obtained at the same treatment over the two years. The control, without fertilizer, showed significantly longer days to flower compared with other treatments in the two years. Conclusion The highest yield obtained at PM 10.0 t/ha +FF was not significantly different from PM 7.5 t/ha +FF. Hence, poultry manure applied at 7.5 t/ha +FF is therefore recommended.